Performance Indicators of Reverse Logistics Systems: A Proposal For A Model Applied to the Brazilian Context - Radzinski, Ana Paula Nascimento; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues; Kobs, Fabio Fernando; Vieira, Cleide (Revista de Gestão Social e Ambiental, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista de Gestão Social e Ambiental (e-ISSN: 1981-982X) ON 2025-02-24, AVAILABLE ONLINE: https://doi.org/10.24857/rgsa.v19n2-088 Abstract Objective: This study aims to propose a universal model of performance indicators (PIs) for Reverse Logistics Systems (RLS). It explores four key topics: quantities of products produced, estimates of product lifespan, consumers' preferences for the disposal or destination of waste, and the amounts of waste returned by the RLS compared to environmental standards for the products. Theoretical Framework: This section presents a compilation of RLS PIs extracted from the literature, categorized into different groups, along with their respective calculation metrics. Method: The methodology used combines a qualitative and quantitative approach, involving bibliographic research and data collection through a survey aimed at representatives of the nine RLS with nationwide coverage included in the study. Results and Discussion: The construction of the results involved compiling and analyzing feedback from the RLS managers, as well as the research topics of interest. This process revealed categories of PIs not previously used by the referenced RLS and culminated in presenting a proposal for a model applied to the Brazilian context. Research Implications: The practical and theoretical implications of the presented proposal promote a more comprehensive view of the topic, uncovering numerous possibilities for direction and improvements in this field. Originality/Value: This study added to the literature by broadening the understanding of variables involved in the RL problem. The importance and value of this research are demonstrated by listing different IDs for SLR, providing guidance, and developing improvement strategies.
Keywords: Reverse Logistics; Performance Evaluation; Performance Indicators; Reverse Logistics Systems; Generic Model